Pulmonary Granuloma Is Not Always the Tuberculosis Hallmark: Pathology of Tuberculosis Stages in New World and Old World Monkeys Naturally Infected with the Mycobacterium tuberculosis Complex. (November 2022) - Pereira, Asheley H.B.; Lopes, Claudia A.A.; Pissinatti, Thalita A.; Pinto, Ana C.A.; Oliveira, Daniel R.A.; Leal, Gabriel M.; Oliveira, Luís C.M.; Redner, Paulo; Barbosa, Bruna E.P.; Moreira, Silvia B.; Pissinatti, Alcides; Maruyama, Fernanda H.; et al.
Summary: We present the pathology of monkeys naturally infected with Mycobacterium tuberculosis complex from five different colonies in Rio de Janeiro, Brazil. On the basis of gross and histopathological findings, the lesions were classified into chronic-active, extrapulmonary, early-activation or latent-reactivation stages. Typical granulomatous pneumonia was seen in 46.6% of cases (six rhesus monkeys [ Macaca mulatta ] and one Uta Hick's bearded saki [ Chiropotes utahickae ]). The absence of pulmonary granulomas did not preclude a diagnosis of tuberculosis (TB): classical granulomatous pneumonia was observed in the chronic-active and latent-reactivation stages but not in the extrapulmonary and early-activation stages. The early-activation stage was characterized by interstitial pneumonia with a predominance of foamy macrophages and molecular and immunohistochemical evidence of M. tuberculosis complex infection. TB should be considered as a cause of interstitial pneumonia in New World Monkeys. We recommend the use of immunohistochemistry and molecular analysis for diagnosis of TB, even when typical macroscopic or histological changes are not observed. Graphical abstract: Image 1